Studies On Some Genetic And Nongenetic Factors Affecting Lactation Period In Gir Cows - Rajoriya, Ravi; Tomar, S.S.; Saha, D. N.; Rajoriya, Shweta; Kumar, Amit (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A total of 599 records of lactation period on 191 Gir cows maintained at Kasturba Gandhi Memorial Trust, Indore, M. P. over a period of 36 years (1974-2009) were analyzed by least squares technique of fitting constants to estimate the effect of sire, period of calving, season of calving, parity and inbreeding. The overall least squares mean of lactation period was found to be 303.28 ± 5.67 days. The results revealed that sire (p<0.05), period of calving (p<0.01), parity (p<0.01) and level of inbreeding (p<0.01) had significant effect on lactation period while the effect of season of calving was non-significant. Inbred cows were found to have significantly shorter lactation period as compared to non-inbred cows. Thus, it can be inferred that inbreeding had deteriorating effect on lactation period in the present herd and hence it should be avoided by formulating proper breeding plan along with other ameliorative managerial practices.